Surface nanostructure optimization for GaAs solar cell application - Hong, Lei (2013)
Numerical simulation of optical absorption characteristics of gallium arsenide (GaAs) thin-film solar cells by the three-dimensional finite element method is presented, with emphasis on optimizing geometric parameters for nanowire and nanocone structures to maximize the ultimate photocurrent under AM1.5G illumination. The nanostructure-based GaAs thin-film solar cells have demonstrated a much higher photocurrent than the planar thin films owing to their much suppressed reflection and high light trapping capability. The nanowire structure achieves its highest ultimate photocurrent of 29.43 mA/cm2 with a periodicity (P) of 300 nm and a wire diameter of 180 nm. In contrast, the nanocone array structure offers the best performance with an ultimate photocurrent of 32.14 mA/cm2. The results obtained in this work provide useful guidelines for the design of high-efficiency nanostructure-based GaAs solar cells.